Forces Influencing Poor Performance of Serbian Food Industry - Nikolic, Ivan; Brankov, Tatjana (Industrija, 2018)
The main objective of this paper is to consider the factors that led to the poor performances of the Serbian agribusiness sector in recent years. Moreover, specific objectives are to discuss the productivity trends in agribusiness sector, to evaluate statistical significance of several important determinants like insufficient domestic demand, low product quality, slow technological changes as well as inadequate state support, and to suggest ways to overcome challenges. A methodology used in the analysis and the results can be employed in a number of ways. It should be noted that panel analysis provides a framework for easy interpretation of determinants that affect the performance of agribusiness sector but also serves as a good empirical confirmation of their statistical significance. On the other hand, the results have implications for the food industry and policy decision making process, as they provide evidence on the current and projected economic performance of food manufacturing industry.